Pengaruh Model Pembelajaran Cooperative Script Berbantuan Media Strip Story terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Matematika Kelas V Sekolah Dasar - Nabilah Sepliana; Allen Marga Retta; Puji Ayurachmawati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The problem of this research is based on the problems that occur, namely the low critical thinking abilities of students in Mathematics learning which is caused by the use of less varied learning models and the minimal use of learning media. This research aims to determine the influence of the Cooperative Script learning model assisted by Strip Story media on students' critical thinking abilities in fifth grade elementary school mathematics subjects. This research uses Quasi Experimental Design research with the Nonequivalent Control Group Design model. The subjects of this research were 30 class V students at SD Negeri 137 Palembang. The data collection method uses tests. The test instrument is a 4-question essay to measure students' critical thinking abilities. The data analysis technique uses independent sample t-test. This can be seen from the results of the Independent Sample T-Test showing a significant difference in values ​​from the mean pretest and posttest data. Then, it can be seen that the p-output significant value (0.000) is lower than the significant level value of 0.05 (95% confidence level), and the t-test value (4.061) shows a higher value than the ttable value (t0.05, 28 =1.701). So it can be concluded that there is an influence of the application of the Cooperative Script learning model assisted by Strip Story media on students' critical thinking abilities in fifth grade elementary school mathematics subjects. In other words, the null hypothesis test (H0) is rejected, while the alternative hypothesis (Ha) can be accepted.